Utilization of Information Technology-Based Learning Media for Supporting Active Learning Activities at Middle School (SMP) Negeri 2 Pantai Labu - Syahputra, MR; Mardiningsih; Rambe, Isnaini Halimah (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The community service that will be carried out in this research is entitled "The Use of Information Technology-Based Learning Media to Support Active Learning Activities in Junior High School (SMP) Negeri 2 Pantai Labu", with the aim of helping teachers in a more interesting, interactive and learning process. fun. In this service activity, teachers will be equipped with the ability to make teaching materials based on information technology. Not only that, teachers will also be equipped with teaching aids that will support active learning activities in schools that can be used for learning mathematics and science. This activity is expected to increase interest in learning and the achievement of teachers and students at SMP Negeri 2 Pantai Labu.